Accurate 14NH3 line-list for the 2.3 μm spectral region. (November 2021) - Čermák, P.; Cacciani, P.; Cosléou, J.
Highlights: Laser absorption spectrum of ammonia recorded at 167, 210 and 396K is analyzed near 2.3 μ m. ? Enhanced multi-temperature technique was used to determine the experimental value of transition lower states. ? 807 ammonia lines are measured in the 4275 - 4356 cm-1 region. ? Intensity based combination difference relations were used to assign over 99.9% of 14NH3 integrated absorption. ? 703 lines are assigned to 23 vibrational bands providing 340 new experimental energy levels. ? The obtained data will be valuable to identify NH3 lines in the 2.3 μ m atmospheric window. Abstract: The narrow linewidth Vertical External Cavity Surface Emitting Laser (VECSEL) was used to record the high-resolution ammonia spectra in the 2.3 μ m atmospheric transparency window at temperatures from 160 to 296 K. In the 4275-4356 cm − 1 ( ∼ 2295-2339 nm) range 807 transitions were identified as belonging to the 14 NH 3, extending our previous room temperature study of 340 transitions. The temperature dependence of line absorbance was used to retrieve the lower state energy for 682 transitions. By comparing the variationally computed line list and exploiting the lower state combination differences relations, the quantum assignment was proposed for 703 lines representing over 99.9% of integrated 14 NH 3 absorption in the range. These transitions reached 611 different upper state levels belonging to 23 vibrational bands. For 340 of them, their experimental energy value was retrieved for the first time. The comparison of our line list to the HITRAN2016 and HITRAN2020 is presented and discussed.